Effects of egg yolk lecithin/milk fat globule membrane material ratio on the structure and stability of oil-in-water emulsions. (1st October 2022) - Yu, Xiaoxue; Zhao, Yanjie; Sun, Meng; Liu, Lu; Li, Xiaodong; Zhang, Xiuxiu; Sun, Yue; Bora, Awa Fanny Massounga; Li, Chunmei; Leng, Youbin; Jiang, Shilong
Abstract: The stability and structure of fat globules are crucial factors affecting the stability of fat in infant formulas and their inherent digestibility and absorption in infants. Thus, the study of mimicking milk fat globule (MFG) emulsions can provide a foundation for the optimization of fats in infant formulas. This study examined the effects of the ratio of egg yolk lecithin (EYL) to milk fat globule membrane (MFGM) material on the stability and fat globule structure of the emulsions. The results show a 1:1 ratio of EYL to MFGM material led to an emulsion with the highest encapsulation rate (90.07 ± 1.03%) and physical stability, larger particle size (1.514 ± 0.043 μm), and the most uniform distribution. Interestingly, formulation at a 1:1 ratio also resulted in the formation of MFG-like structures with phospholipids and proteins encapsulating the lipid core. Moreover, as the ratio of EYL to MFGM material increased, the casein and whey protein content at the simulated fat globule interface decreased, while the phospholipid content increased. Therefore, the addition of EYL represents a promising strategy to enhance the fat globule structure of the MFGM material and increase the stability of the emulsion. Highlights: This study also aimed to help the dairy industry by identifying alternative ingredients to milk fat globule membrane. The milk fat globule membrane materials and egg yolk lecithin had advantages in terms of composition and bioavailability. A more stable emulsion was prepared by adjusting the ratio of egg yolk lecithin to milk fat globule membrane. The lecithin supplementation improved the composition of the fat globule interfacial proteins.